Sex‐ and Gender‐specific Research Priorities in Cardiovascular Resuscitation: Proceedings from the 2014 Academic Emergency Medicine Consensus Conference Cardiovascular Resuscitation Research Workgroup. (December 2014) - Wigginton, Jane G.; Perman, Sarah M.; Barr, Gavin C.; McGregor, Alyson J.; Miller, Andrew C.; Napoli, Anthony F.; Safdar, Basmah; Weaver, Kevin R.; Deutsch, Steven; Kayea, Tami; Becker, Lance; Miner, James
Abstract Significant sex and gender differences in both physiology and psychology are readily acknowledged between men and women; however, data are lacking regarding differences in their responses to injury and treatment and in their ultimate recovery and survival. These variations remain particularly poorly defined within the field of cardiovascular resuscitation. A better understanding of the interaction between these important factors may soon allow us to dramatically improve outcomes in disease processes that currently carry a dismal prognosis, such as sudden cardiac arrest. As part of the 2014 Academic Emergency Medicine consensus conference "Gender‐Specific Research in Emergency Medicine: Investigate, Understand, and Translate How Gender Affects Patient Outcomes, " our group sought to identify key research questions and knowledge gaps pertaining to both sex and gender in cardiac resuscitation that could be answered in the near future to inform our understanding of these important issues. We combined a monthly teleconference meeting of interdisciplinary stakeholders from largely academic institutions with a focused interest in cardiovascular outcomes research, an extensive review of the existing literature, and an open breakout session discussion on the recommendations at the consensus conference to establish a prioritization of the knowledge gaps and relevant research questions in this area. We identified six priority research areas: 1) out‐of‐hospital cardiac arrest epidemiology and outcome, 2) customized resuscitation drugs, 3) treatment role for sex steroids, 4) targeted temperature management and hypothermia, 5) withdrawal of care after cardiac arrest, and 6) cardiopulmonary resuscitation training and implementation. We believe that exploring these key topics and identifying relevant questions may directly lead to improved understanding of sex‐ and gender‐specific issues seen in cardiac resuscitation and ultimately improved patient outcomes.